The Battle of Images on Instagram: Comparison Analysis on Impression Management Strategies of Indonesian Presidential Candidates in the 2024 Election - Inri Inggrit Indrayani (Jurnal Komunikasi, 2025)
Social media, particularly Instagram, has become a key platform for political candidates to construct public personas and influence voters. In the context of Indonesia’s 2024 presidential election, the strategic use of visual communication plays a crucial role in shaping public impressions, especially among Gen Z voters. This research aims to identify the impression management strategies implemented by the three presidential candidates in Indonesia on Instagram during the 2024 presidential election. As one of the social media platforms, Instagram has been utilized to present self-presentation verbally and visually. Message management strategies from the perspective of political public relations are not merely communication practices constructed for political purposes; rather, they are a deliberate planning process designed to achieve the desired image and reach constituents, particularly Generation Z, which currently dominates the number of voters in Indonesia and is also active users of Instagram. This study employs a content analysis of the Instagram posts from the three candidates from the beginning to the end of the campaign, specifically from November 28, 2023, to February 10, 2024. The results of this study indicate that the impression management strategy used by Anies Baswedan is the Self-Image Confirmation Strategy (53.5%), the Affinity-Seeking and Politeness Strategy (25.8%), followed by Credibility (1.6%), and lastly, Influence (19.1%). Prabowo Subianto employs the Affinity-Seeking and Politeness Strategy (47%) as the most frequently used, along with the Self-Image Confirmation Strategy (27.1%). Prabowo also utilizes the Influence Strategy (20.7%) and the Credibility Strategy (5.2%), with a higher percentage compared to his two political opponents. Similarly, Ganjar Pranowo uses the Affinity-Seeking and Politeness Strategy (51.9%), the Self-Image Confirmation Strategy (44.7%), and the Influence Strategy (3.4%).